PENGARUH MODEL PROJECT BASED LEARNING BERBANTUAN MEDIA VLOG TERHADAP KETERAMPILAN MENULIS TEKS BERITA SISWA KELAS XI SMA NEGERI 1 LENGAYANG - Intan Mairiza Putri; Emidar (EDU RESEARCH, 2024)
This study has three objectives to explain the influence of the Project Based Learning model assisted by vlog media on the news text writing skills of grade XI students of SMA Negeri 1 Lengayang. This type of research is quantitative with a quasy experimental research design or also known as a mock research. The method used is descriptive analytical. In this study, the design or design used is One Group Pretest-posttest Designe. The population of this study is class XI of SMA Negeri 1 Lengayang which is spread from XI F1 to F8. The research sample was selected based on the purposive sampling technique. The research sample was selected based on the purposive sampling technique. The sample used was only one class, namely class XI F1. Based on the t-test, the alternative hypothesis (H1) was accepted at the level of trust and degree of freedom (dk) = (n-1) because of the tcal>ttable (6.92 > 1.68) thus, the learning outcomes of news text writing skills of grade XI students of SMA Negeri 1 Lengayang using the Project Based Learning model assisted by vlog media were higher than using the conventional learning model. Based on the results of the study, it can be concluded that the Project Based Learning model assisted by vlog media has an effect on the news text writing skills of grade XI students of SMA Negeri 1 Lengayang.